Effect of retirement on self-rated oral health and dental services use: longitudinal fixed-effects instrumental variable study in 31 countries - Sebastian-Edgar Baumeister; Hanna Wesselmann; Gustavo G Nascimento; Stefan Listl (Nordic Association of Occupational Safety and Health (NOROSH), 2024)
OBJECTIVE: This study examined the effect of retirement on self-rated oral health and dental services use. METHODS: Covering 31 countries, we used harmonized panel data from the English Longitudinal Study on Aging (ELSA), Health and Retirement Study (HRS), and the Survey of Health, Aging and Retirement in Europe (SHARE). Data comprised 485 085 observations from 112 240 individuals aged ≥50 years. Official and early retirement ages were leveraged as instruments in a fixed-effects instrumental variable approach. RESULTS: We found that retirement exhibited a negative effect on self-rated oral health (β = -0.37; 95% confidence interval (CI) -0.44- -0.30) and a positive effect on the propensity to seek dental care (β = 0.56; 95% CI 0.53-0.60). Male retirees showed a stronger decrease in self-rated oral health and increase in dental services use than female retirees. Participants who previously worked in a physically demanding job showed a stronger effect on self-rated oral health. Conversely, participants without a physically demanding job in the past exhibited a stronger retirement effect on dental service use. Compared with other health system clusters, retirement effects on dental services use were stronger in three health system clusters: Belgium, Denmark, Finland, France, Ireland, Luxembourg, The Netherlands, and Sweden; Israel; and the United States. CONCLUSIONS: Using a quasi-experimental design, we found that transition to retirement lowers self-rated oral health and increases the use of dental services. Retirement effects appeared heterogeneous across sexes, type of previous labor, and health systems.